Toward a Global Genomic Epidemiology of Meningococcal Disease. (31st October 2019) - Retchless, Adam C; Fox, LeAnne M; Maiden, Martin C J; Smith, Vincent; Harrison, Lee H; Glennie, Linda; Harrison, Odile B; Wang, Xin
Abstract: Whole-genome sequencing (WGS) is invaluable for studying the epidemiology of meningococcal disease. Here we provide a perspective on the use of WGS for meningococcal molecular surveillance and outbreak investigation, where it helps to characterize pathogens, predict pathogen traits, identify emerging pathogens, and investigate pathogen transmission during outbreaks. Standardization of WGS workflows has facilitated their implementation by clinical and public health laboratories (PHLs), but further development is required for metagenomic shotgun sequencing and targeted sequencing to be widely available for culture-free characterization of bacterial meningitis pathogens. Internet-accessible servers are being established to support bioinformatics analysis, data management, and data sharing among PHLs. However, establishing WGS capacity requires investments in laboratory infrastructure and technical knowledge, which is particularly challenging in resource-limited regions, including the African meningitis belt. Strategic WGS implementation is necessary to monitor the molecular epidemiology of meningococcal disease in these regions and construct a global view of meningococcal disease epidemiology.